(3QHj GdHGbjs - (3GOGf, YGFTIs; (3GdZGfe, MhQs; (3YcGhj, QMGHs; (3cfYGf, CMeOs ((3GdOGQ GdHjVGA, GdeZQHs (3OGQ GdKbGaI ddfTQ hGdJhRjYs, 2024)
(3GdHGbj gh GdPj dG jehJ hdG jfJgj, gh GdPj dG jfbWY CHOkG(B. (3GdHGbj gh Gddg hMOg(B. (3hdcf QHfG jMjj GdehJi aj GdBNQI(B. (3Efg jYjO GdMjGI EdjfG hEdi CMHGFfG aj GdBNQI, Efg Ydi cd TF bOjQs
(3JQHjI OjfjIs
Keywords: (3GdOjfs